Preliminary Experience With the New Amplatzer™ Trevisio™ Delivery System in Transcatheter Atrial Septal Defect Closures in Children - Haddad, Raymond N.; Khraiche, Diala; Bonnet, Damien; Meot, Mathilde; Malekzadeh-Milani, Sophie (Frontiers in Pediatrics, 2021)
Objectives: To evaluate safety, efficacy, and technical advantages of Amplatzer™ Trevisio™ intravascular delivery system (ATIDS) in percutaneous atrial septal defect (ASD) closure in children. Background: The Trevisio™ is a novel delivery system designed for accurate and facilitated implantation of Amplatzer™ devices. There are no published clinical reports so far. Methods: During September 2020, 9 children with anatomically challenging ASDs underwent attempted transcatheter closure using ATIDS to deliver Amplatzer™ Septal occluders (ASO). All interventions were performed under general anesthesia, trans-oesophageal echocardiography (TOE), and fluoroscopic guidance. Standard safety, immediate, and 60-days outcomes were prospectively assessed. Results: The median age was 8.1 (5.1 to 16.9) years and the median bodyweight was 30 (18 to 63) kg. Six patients had isolated secundum-type ASDs with absent anterosuperior rims including one with an aneurysmal septum. Three patients had unclassical defects associated with complex congenital heart anomalies. Eight devices were delivered from the femoral vein and the jugular vein was accessed in one patient with interrupted inferior vena cava and azygos continuation. All implantations were successful. The shape, position, and orientation of the ASO were identical before and after release on TOE and fluoroscopy. There was no device embolization or serious complication following closure. Complete shunt closure was confirmed on follow-up. Conclusions: We report the first clinical experience with AITDS in transcatheter ASD pediatric closures. Safety and efficacy were witnessed in our case-series. The major advantage of reduced-tension deployment and reliable precision in device positioning is highly beneficial in challenging anatomies and unusual access.